REVES: Editorial Review Board / Corpo de Avaliadores/ Lista de Evaluadores 2021/2022 - Antonio Marcos de Oliveira Siqueira; Wagner dos Reis Marques Araujo; Aldair Oliveira de Andrade; Roberta Ferreira Coelho de Andrade (REVES - Revista Relações Sociais)
Editorial Review Board / Corpo de Avaliadores/ Lista de Evaluadores 2021/2022